"That sounds about right"--Lexical bundle naturalness intuitions in Japanese learners of English - Julian Northbrook; Kathy Conklin (Vocabulary Learning and Instruction)
The current study examines the perceived naturalness of lexical bundles learned from early-stage teaching materials in Japanese learners of English. Naturalness ratings of 24 native English speakers and 23 non-native speakers with Japanese as their first language were compared in relation to corpus derived frequencies from the British National Corpus (BNC) and a corpus of Japanese secondary-school English textbooks–the “Junior High School English Textbook Corpus” (JHSETC, Northbrook & Conklin, 2018). The rating scores of both groups were significantly predicted by lexical bundle frequency. However, the groups were sensitive to different metrics, the performance of native speakers was best predicted by the BNC, and that of the Japanese speakers by the JHSETC. This is taken as evidence that learner intuitions are affected by the input they receive from teaching materials, and that these intuitions may stay with learners long term